Comparison of the primary and secondary stability of implants with anodized surfaces and implants treated by acids: A split-mouth randomized controlled clinical trial - de Oliveira, Guilherme José Pimentel Lopes (2016)
Purpose: The objective of this randomized controlled clinical split-mouth trial was to compare anodized implant surfaces and implant surfaces modified by acid etching in terms of primary and secondary stability. Materials and Methods: Forty-six implants were placed bilaterally in the posterior mandibles of 23 patients. Each patient received one implant with a surface treated by acid (AC) and the other with an anodized implant surface (ANO). The selection of the side where the implant was placed was chosen randomly by lot. The implants were evaluated with respect to insertion torque within the surgical bed and primary and secondary stability by testing the implant stability quotient (ISQ) at five different times (immediate postoperative period and 21, 30, 60, and 180 days after surgery). The paired t test was used to compare the two groups, and ANOVA Repeated Measures complemented by the Tukey posttest were used for longitudinal analysis of the implants in each group. All tests were applied with a confidence level of 95% (P < .05). Results: No statistically significant difference was detected between the AC and ANO groups regarding insertion torque. ISQ analysis revealed that the AC group showed statistically higher values than the ANO group at the 21-day period (P <.05); however, no other statistically significant differences were detected at the other times. Conclusion: The different surfaces were similar in terms of primary and secondary stability of implants placed in the posterior mandible.